Family Constellation and Law: the new path to social peace (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This article aims to present notions about Systemic Law, i.e. the application and verification of Laws and Orders according to the Philosophy of Family Constellation created by the German Bert Hellinger. It is a model available to other areas of knowledge that has already achieved significant results in resolving conflicts in court, including awards from the National Council of Justice. The technique points to a new and effective way of delivering justice, where the parties leave the Judiciary internally reconciled, avoiding the filing of new lawsuits.
Keywords: systemic law; family constellation; conflict resolution; conciliation; mediation; peace